The Impact of "Collaborative Team” Working System as an Effort of Creative Design in TSDSIA - Nava, Lidya; Valencia, Phebe (Jurnal Strategi Desain dan Inovasi Sosial, 2023)
TSDSIA is a design firm engaged in interior and architecture since 2011. TSDSIA provides consulting services in Indonesia led by Tony Sofian (from now on, referred to as TS). TSDSIA uses a "collaborative team" working system to perform the creativity process. This collaboration work system represents a work method that is incapable of being avoided and is not used more at this point. Collaboration is a strategy that can leverage individual and collective knowledge to achieve results that may never have been imagined before[A2]. Collaboration also creates more interesting, challenging, and enjoyable working conditions in achieving the results of design creativity. Although in the process, it takes a lot of investment from time and resources (financial and human), if used appropriately, the collaboration will be a profitable investment. The research method in this paper uses a qualitative approach by using an ethnographic research approach through direct field observation and interview methods. The authors' used instrument case study methods and data processing techniques (data reduction, data presentation, conclusion withdrawal) to analyses the data. The purpose of this discussion is to find out the relationship between the four components of creativity in post- pandemic TSDSIA and their effect on employee design creativity to produce a quality design in terms of aesthetic, functional and best architectural and the interior experience in each project being worked on more post-pandemic. Ultimately, this study sees the influence of the "collaborative team" work system as an effort of design creativity in TSDSIA.